2004
DOI: 10.1074/jbc.m311844200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-induced Astrocytic Differentiation of C6 Glioma Cells Is Mediated by Autocrine Interleukin-6

Abstract: Elevation in the level of intracellular cAMP is known to induce the astrocytic differentiation of C6 glioma cells by unknown mechanisms. In this report, we show that cAMP-induced autocrine interleukin 6 (IL-6) promoted astrocytic differentiation of C6 cells. Treatment of cells with N 6 ,2 -O-dibutyryl cAMP (Bt 2 AMP) and theophylline caused the delayed phosphorylation of signal transducer and activator of transcription 3 (STAT3), as well as the expression of an astrocyte marker, glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 35 publications
7
74
0
Order By: Relevance
“…3B). Thus, cAMP has been shown to alter the morphology of primary cortical precursor cells and glioma cells [13,22]. Our results suggested that cAMP acts in B92 cells to induce morphological changes within 72 h of the stimuli (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…3B). Thus, cAMP has been shown to alter the morphology of primary cortical precursor cells and glioma cells [13,22]. Our results suggested that cAMP acts in B92 cells to induce morphological changes within 72 h of the stimuli (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, intracellular cAMP seems to play an important role in controlling differentiation and proliferation [13,22]. However, the signaling cascade involved in the cAMP-regulated proliferation has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cells expressing high level of IEX-1 were no longer flat but rather rounded with longer processes, characteristic of cells exhibiting astrocytic phenotypes. The levels of S-100 protein and GFAP, glial differ- entiation markers [Tabuchi et al, 1981;Takanaga et al, 2004], increased directly proportional to that of IEX-1. From these results, we speculated that IEX-1 might be implicated in differentiation of glioma cells.…”
Section: Iex-1 Overexpression Leads To Astrocytic Differentiation Of mentioning
confidence: 94%
“…In the present study, we have attempted to test the possibility that IEX-1 might enhance apoptosis of human glioma cells induced by therapeutic treatments, such as chemotherapeutic agents and g-ray. Unexpectedly, however, we found that U87-MG human glioma cells overexpressing IEX-1 underwent morphological changes to astrocytic phenotype and increase in glial differentiation marker proteins, S-100 [Tabuchi et al, 1981] and glial fibrillary acidic protein (GFAP) [Takanaga et al, 2004]. Elevated cAMP and the consequent activation of protein kinase A (PKA) appeared to differentiate U87-MG glioma cells to express astrocytic phenotype, as previously observed in rat C6 glioma cell line [Willingham, 1976;Yoshimura et al, 1997;Takanaga et al, 2004], which is often used as a model system of glial cell differentiation [Harris et al, 1980].…”
mentioning
confidence: 92%
“…Cholera toxin catalyzes ADP-ribosylation of Gs protein and results in accumulation of cellular cAMP (11,12). Ample evidence indicates that cAMP-elevating stimuli such as N-substituted cAMP analogues and cAMP-increasing reagents can induce cell differentiation in gliomas (13,14). Guerrant et al (15) reported that active whole cholera toxin, but not inactive choleragenoid, produces elevation of cAMP and parallel morphological changes in CHO cells.…”
mentioning
confidence: 99%